Electronic voting : second International Joint Conference, E-Vote-ID 2017, Bregenz, Austria, October 24-27, 2017, proceedings /: second International Joint Conference, E-Vote-ID 2017, Bregenz, Austria, October 24-27, 2017, proceedings. (2017) - Unknown
No abstract available